Associations between smoking and clinical outcomes after total hip and knee arthroplasty: A systematic review and meta-analysis - Yue, Chen; Cui, Guofeng; Ma, Maoxiao; Tang, Yanfeng; Li, Hongjun; Liu, Youwen; Zhang, Xue (Frontiers in Surgery, 2022)
Background: Smoking increases risk of several complications after total hip or knee arthroplasty (THA/TKA), so we systematically reviewed and meta-analyzed the literature to take into account all relevant evidence, particularly studies published since 2010. Methods: The PubMed, Ovid Embase, Web of Science, and EBSCOHost databases were searched and studies were selected and analyzed according to MOOSE recommendations. Methodological quality of included studies was assessed using the Newcastle-Ottawa Scale. Data were qualitatively synthesized or meta-analyzed using a random-effects model. Results: A total of 40 studies involving 3,037,683 cases were included. Qualitative analysis suggested that smoking is associated with worse patient-reported outcomes within one year after surgery, and meta-analysis showed that smoking significantly increased risk of the following outcomes: total complications (OR 1.41, 95%CI 1.01-1.98), wound complications (OR 1.77, 95%CI 1.50-2.10), prosthetic joint infection (OR 1.84, 95%CI 1.52-2.24), aseptic loosening (OR 1.62, 95%CI 1.12-2.34), revision (OR 2.12, 95%CI 1.46-3.08), cardiac arrest (OR 4.90, 95%CI 2.26-10.60), cerebrovascular accident (OR 2.22, 95%CI 1.01-4.85), pneumonia (OR 2.35, 95%CI 1.17-4.74), acute renal insufficiency (OR 2.01, 95%CI 1.48-2.73), sepsis (OR 4.35, 95%CI 1.35-14.00), inpatient mortality (OR 12.37, 95%CI 4.46-34.28), and persistent opioid consumption (OR 1.64, 95%CI 1.39-1.92). Conclusion: Smoking patients undergoing THA and TKA are at increased risk of numerous complications, inpatient mortality, persistent opioid consumption, and worse 1-year patient-reported outcomes. Pre-surgical protocols for these outcomes should give special consideration to smoking patients.